2011
DOI: 10.1088/0031-9155/56/10/016
|View full text |Cite
|
Sign up to set email alerts
|

A polygon-surface reference Korean male phantom (PSRK-Man) and its direct implementation in Geant4 Monte Carlo simulation

Abstract: Even though the hybrid phantom embodies both the anatomic reality of voxel phantoms and the deformability of stylized phantoms, it must be voxelized to be used in a Monte Carlo code for dose calculation or some imaging simulation, which incurs the inherent limitations of voxel phantoms. In the present study, a voxel phantom named VKH-Man (Visible Korean Human-Man), was converted to a polygon-surface phantom (PSRK-Man, Polygon-Surface Reference Korean-Man), which was then adjusted to the Reference Korean data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 20 publications
0
66
0
Order By: Relevance
“…It requires modelling of a radiation source, the general interaction processes of the particles being transported, the media in which the transport is performed, and how and where the individual particles are being tallied. Applications for radiation transport simulation are, for example, treatment planning for radiotherapy, computed tomography simulation, and reconstruction of radiological accidents (Kling et al 2001).…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires modelling of a radiation source, the general interaction processes of the particles being transported, the media in which the transport is performed, and how and where the individual particles are being tallied. Applications for radiation transport simulation are, for example, treatment planning for radiotherapy, computed tomography simulation, and reconstruction of radiological accidents (Kling et al 2001).…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…• Kim et al (2011) use graphic modelling tools to approximate a voxel model with a mixture of polygon and NURBS meshes. …”
Section: Hybrid Modelsmentioning
confidence: 99%
“…A version of Geant4 is available for direct implementation of PM phantoms, resulting, however, in high computation times. 8 To improve computation speed, Yeom et al 25 converted PM phantoms to a tetrahedral mesh format via tetrahedralization for use in the Monte Carlo code GEANT4. Moreover, PenMesh, a Monte Carlo code based on PENELOPE physics subroutines, can directly deal with PM geometries.…”
Section: Whole Body Voxel Model Laura and Its Nurbs/pm Versionmentioning
confidence: 99%
“…The third generation of phantoms is the so-called hybrid type; the organs are described by either NURBS or PM surfaces. [6][7][8] This offers both flexibility in organ alterations and anatomical realism. While most of the hybrid phantoms were applied for dosimetry, Segars et al 9 generated 58 adult highly detailed 4-D extended cardiac-torso (XCAT) phantoms based on patient CT data to be used for imaging research.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their geometric features, computational models can be divided into three basic categories: stylized models which employ simple equationbased mathematical functions, voxel-based models which use matrices obtained from segmented medical images, and boundary representation (BREP) models which employ nonuniform rational B-splines (NURBS) or polygonal meshes to represent the surface contour of individual organs and the whole body. [23][24][25][26] In most studies reported in the literature, the estimation of organ absorbed dose for a spectrum of populations of different ages from radiopharmaceuticals used in nuclear cardiology was performed using mathematical phantoms, [27][28][29] voxel-based models of the same subject.…”
Section: Introductionmentioning
confidence: 99%